Food sources for the Ediacara biota communities - Bobrovskiy, Ilya (Nat Commun, 2020)
The Ediacara biota represents the first complex macroscopic organisms in the geological record, foreshadowing the radiation of eumetazoan animals in the Cambrian explosion. However, little is known about the contingencies that lead to their emergence, including the possible roles of nutrient availability and the quality of food sources. Here we present information on primary producers in the Ediacaran based on biomarker molecules that were extracted from sediments hosting Ediacaran macrofossils. High relative abundances of algal steranes over bacterial hopanes suggest that the Ediacara biota inhabited nutrient replete environments with an abundance of algal food sources comparable to Phanerozoic ecosystems. Thus, organisms of the Ediacara biota inhabited nutrient-rich environments akin to those that later fuelled the Cambrian explosion.